Wireless mesh networking - Tan, Ethel Mei Shuang (Nanyang Technological University, 2022)
The applications of WiFi technology have been increasingly explored, with WiFi localisation becoming a popular area of interest. However, current commercial off-the-shelf(COTS) WiFi localisation technology is unable to keep up with the latest WiFi standards and does not utilise Channel State Information(CSI) technology from new WiFi protocols that support a larger bandwidth. Additionally, they are unable to maintain their accuracy under non-line-of-sight(NLOS) conditions.